Konsep Presidensial Threshold terhadap Demokrasi di Indonesia - Lutfi Yusup Rahmathoni; Sri Herlina (Jurnal Hukum Lex Generalis, 2025)
Presidential Threshold in Indonesia’s democratic system focuses on its alignment with the principles of democracy as stipulated in the 1945 Constitution of the Republic of Indonesia. The Presidential Threshold is a provision that sets a minimum requirement for nominating presidential and vice-presidential candidates. Although argued to simplify the contest and maintain governmental stability, this policy is considered contrary to democratic principles that uphold freedom, equality, and public representation. This study employs a juridical-normative method with an approach based on democratic theory and statutory regulations. The findings indicate that the implementation of the Presidential Threshold presents a dilemma between forming a strong and stable government and the importance of maintaining openness to diverse political participation. While the policy aims to streamline the electoral system, in practice it may violate democratic principles, particularly regarding the protection of the right to be elected, and contradict the principles of representation, freedom to run for office, and fairness in a pure democracy. Therefore, it is necessary to establish new regulations to balance the goal of political stability with the principle of popular sovereignty.